ENGINEERING STUDENTS VS TEACHING ENGLISH USED FOR LIFE SKILLS - Dr.Venugopal Naidu. Mamidi (Galaxy International Interdisciplinary Research Journal, 2023)
Andhra Pradesh has become prominent in many fields to day because its a new state. Andhra Pradesh is a place of assortment and creating new environment. Different people speak different language slangs and dialects. However students can understand in English. Hence English is a bridge language. Different locality people can feel comfortable in communicating with one another in English. In fact all advanced knowledge in science, technology and medicine is accessible in English. The results of the latest researches come through the medium of English. Today the world has become a global village; it is all because of English. English is an international language. English is the primary source of the Constitution, the Supreme Court, the High Courts and official departments. English is now strongly rooted in the places of A.P. It has become a part of their life. Thus English has great significance for the reliability of A.P. It has to be second language in our country for the better growth of the country. In this paper I tried to cite the trouble faced by English language Teacher, in teaching students of Engineering and Technology, at the same time inconvenience faced by students in learning English.